Investigation of Electronic Resistance in Lithium-Ion Batteries by AC Impedance Spectroscopy. Issue 14 (1st January 2017) - Takeno, Mitsuhiro; Fukutsuka, Tomokazu; Miyazaki, Kohei; Abe, Takeshi
Abstract : Reduction in the internal resistance of lithium-ion batteries (LIBs) is an inevitable task to practical application of LIBs to electric vehicles. In this study, we focused on electronic resistances in composite electrodes derived from conductive materials. As electronic conductive materials, acetylene black and fine graphite particle were used. Electronic resistances of electrode-slurries and composite electrodes with different conductive materials were investigated and it was found that the kind of conductive materials strongly influenced direct current-internal resistances. In the Nyquist plots of symmetric cells, semi-circles assigned to electronic contact resistances at active material/conductive material interface appeared in high-frequency region. Based on the transmission line model, an influence of the electronic contact resistance on charge-transfer resistances was examined.